Green Bond: Financing Alternative for UCO Based Biodiesel Industry - Wirawan, Dimas Andi; Sari, Ira Febriana (JEJAK: Jurnal Ekonomi dan Kebijakan, 2023)
Along with the growing demand of biodiesel, the unlocking potential for using Used cooking oil (UCO) as feedstock, and the abundant amount of UCO, make their utilization becomes relevant. However, such efforts were constrained by economic scales issue, due to supply chain and financing problems. This paper aims to provide references regarding the feasibilty of UCO-based biodiesel project and its financing schemes through green bond. The main focus of this paper's discussion includes project feasibility, business model, and analysis of green bond issuance in financing the industry. The study was carried out by performing integrative literature review method on project feasibility studies in several countries, business model performed in several region, as well as framework and regulation regarding green bonds in Indonesia. Based on the analysis, it can be concluded that the UCO-based biodiesel project is financially and economically feasible to be scaled up. Subseuently, the business model of this industry is fulfilling the green criteria and is eligible to be financed through green bond. Future study regarding the spatial mapping and technical assessment upon the transformation of existing facilities into UCO based biodiesel plants is immensely prominent.